Effects of ALSinhibitor herbicides, crop sequence, and fertilization on natural soil suppressiveness to Striga hermonthica - Emechebe, A.; Berner, D.; Lagoke, S.T.O.; Ahonsi, M. (Elsevier, 2004)
Striga hermonthica remains one of the greatest biological threats to cereal production in the savannahs of sub-Saharan Africa. Control efforts at the International Institute of Tropical Agriculture (IITA), Nigeria, focus on developing integrated S. hermonthica management (ISM) options such as legume-cereal rotation, use of host–plant resistance, soil-based biological control exploiting enhancement of naturally occurring biotic soil suppressiveness, and use of acetolactate synthase (ALS)-inhibiting herbicides as host–crop seed treatments. We investigated, in pots, if soybean crops with or without fertilizer (N, P, or NPK) and preceding a maize crop used as a bioassay enhanced biotic soil suppressiveness to S. hermonthica, and if the ALS-inhibitor herbicides, imazaquin and nicosulfuron, used to control weeds in preceding crops constitute any risk to this biotic system. Factors tested included: (1) crop preceding bioassay maize (soybean [EMGOPA] versuss maize [8338-1]); (2) herbicide weed control in preceding crop (imazaquin in soybean and nicosulfuron in maize versus hand weeding); (3) fertilizer application to preceding crop (90 kg N ha−1, 40 kg P ha−1; 90 kg NPK; versus no fertilizer); (4) soil treatment before planting bioassay maize (pasteurized soil versus non-pasteurized soil). Effects of treatments on biotic suppressiveness were evaluated by comparing effects of treatments in non-pasteurized soil with those of the same treatments in pasteurized soil. Results indicated that biotic soil suppressiveness to S. hermonthica existed naturally in the soil used and was enhanced by a preceding soybean crop and application of N, P or NPK fertilizers. Weed control using ALS-inhibiting herbicides in the preceding crops, particularly imazaquin applied in soybean, had a negative effect on natural soil suppressiveness to S. hermonthica parasitism in maize. Results of this study further confirm the biotic nature of soil suppressiveness to S. hermonthica, and stress its important role in ISM. Land-based management strategies for S. hermonthica control, such as legume crops in rotation to enhance soil N and fertilizer application appear to directly enhance soil suppressiveness to S. hermonthica. Because ALS-inhibiting herbicides pose a risk to biotic soil suppressiveness, their use as a primary control measure for S. hermonthica control in Africa may not be a sustainable approach.